2021
DOI: 10.3390/su13158626
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Potential Risk of Heavy Metal Pollution of Edible Cultivated Plants in Urban Gardening Contexts Using a Citizen Science Approach in the Project “Heavy Metal City-Zen”

Abstract: Urban gardening has become increasingly popular, creating green oases in cities; however, many of these activities are undertaken in areas of high traffic density or on ex-brown field sites. As a consequence, there are still some barriers to the adoption of these urban gardening practices for food production. One of the public concerns is the transfer of urban pollutants such as heavy metals into the consumer’s food chain, however, city-wide data is often difficult and expensive to collect. In the citizen scie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 57 publications
(86 reference statements)
0
6
0
Order By: Relevance
“…Thus, there are many transportation activities for various types of ships. This significantly contributes to exposure to pollutants, especially pollutants of the PAH, HM, and MP types [13,46,101].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, there are many transportation activities for various types of ships. This significantly contributes to exposure to pollutants, especially pollutants of the PAH, HM, and MP types [13,46,101].…”
Section: Discussionmentioning
confidence: 99%
“…According to the Director General of BPOM RI No. 03725/B/SK/VII/89, the maximum threshold value of heavy metal contamination in fish for pollutants Pb +2 and Cu +2 = 0.008 µg/g [33,55,82,101] The data on the average concentrations of the two heavy metal pollutants (Table 7) show that exposure to Pb +2 and Cu +2 is still below the threshold value. However, using the Australian and New Zealand Environment and Conservation Council (ANZECC) standard, with a smaller tolerance value than the maximum threshold, it was concluded that the two pollutants found in fish around BCI exceeded the standard [10,55,76,102,103].…”
Section: Heavy Metal Pollutant Analysismentioning
confidence: 99%
“…Citizens across Vienna Austria were asked to bury pots in which they grew plants. After the growing cycle was completed the citizens collected soil and plant samples to send to the lab for a heavy metal analysis (Ziss et al 2021).…”
Section: Soil Pollutionmentioning
confidence: 99%
“…Comparing the concentration of the measurement results (Table 7) with seawater quality standards shows that the contaminants Pb +2 and Cu +2 , about BCI, are 20 times and 25 times higher, respectively [99]. The maximum threshold value for heavy metal contaminants in fish, Pb +2 = 2 µg/g and Cu +2 = 20 µg/g, by Dirjen BPOM No 03725/B/SK/VII/89 [100]. The average concentration of the two types of heavy metal pollutants (Table 7) shows that exposure to Pb +2 and Cu +2 is still below the threshold value.…”
Section: Heavy Metal Pollutant Analysismentioning
confidence: 99%